(untitled) (Journal of Engineering, 2016)
Different frequency distributions models were fitted to the monthly data of raw water Turbidity at water treatment plants (WTPs) along Tigris River in Baghdad. Eight water treatment plants in Baghdad were selected, with raw water turbidity data for the period (2008-2014). The frequency distribution models used in this study are the Normal, Log-normal, Weibull, Exponential and two parameters Gamma type. The Kolmogorov-Smirnov test was used to evaluate the goodness of fit. The data for years (2008-2011) were used for building the models. The best fitted distributions were Log-Normal (LN) for Al-Karkh, Al-Wathbah, Al-Qadisiya, Al-Dawrah and, Al-Rashid WTPs. Gamma distribution fitted well for East Tigris and Al-Karamah WTPs. As for Al-Wehda WTP Weibull distributions, was the best model. The best fitted distributions were used to forecast ten sets of monthly data for each plant that were compared with the observed data for years (2012-2014). The Kolmogorov-Smirnov test results indicated the capability of these models to produce data that has the same frequency distribution of the observed data. Moreover the frequency of occurrence of the observed and generated series in each plant indicated the capability of the model to produce results with frequency occurrence of probabilities of turbidity values > 50, 80, 100, 120, and 150 NTU.